VD_FINDINFO Jug / 2025 / 208 vom 16. August 2024 - VD Tribunal cantonal (2024)
RECEL, ESCROQUERIE, COMPLICITÉ, CONSTATATION DES FAITS, FIXATION DE LA PEINE | 146 al. 1 CP, 160 ch. 1 al. 1 CP, 25 CP, 47 CP, 10 CPP (CH)